An expanded post-disaster needs assessment about the effects of Typhoon Yolanda on the University of the Philippines Tacloban College Library towards the development of a disaster management plan - Plimaco, Paul Kirby B. (School of Library and Information Studies, University of the Philippines Diliman, 2017)
Cultural institutions like libraries play an important role defining a people's identity and culture. In context to a disaster, libraries help in the rebuilding of a community both culturally and economically. However, disaster planning for libraries in the Philippines have long been a challenge due to budget cuts and the lack of adequate training and programs for disaster resiliency.